The creation of Israel - Margulies, Phillip, 1952- (Detroit : Greenhaven Press : Thomson/Gale, 2005)
Presents a collection of essays that provide a historical overview of the treatment of Jews and discusses the role of various individuals and specific events leading to the creation of the state of Israel in 1948.
Includes bibliographical references (p. 259-260) and index.
Young Adult
Keywords: Zionism -- History; Zionism -- Government policy -- Great Britain -- History; Jews -- Palestine -- Politics and government; Israel-Arab conflicts; Palestine -- Politics and government; Israel -- History